Efeitos do uso de subdoses de herbicidas no controle de diferentes espécies do gênero Urochloa - Guidette, Luiz Gustavo (Universidade Federal de São Carlos, 2024)
In crop-livestock integration systems, the use of underdoses of herbicides has stood out because it makes it possible to manage forage species in consortium with corn. The aim of this study was to evaluate the treatments mesotrione + atrazine (60 + 800, 90 + 800 and 120 + 800 g a.i. ha-1), mesotrione + terbuthylazine (60 + 250, 90 + 250 and 120 + 250 g a.i. ha-1), nicosulfuron + atrazine (16 + 800 and 20 + 800 g a.i. ha-1) and nicosulfuron + atrazine (16 + 800 and 20 + 800 g a.i. ha-1). a ha-1) and nicosulfuron + terbuthylazine (16 + 250 and 20 + 800 g i.a ha-1), in subdoses, regarding the phytotoxicity observed in the species Urochloa brizantha and Urochloa ruziziensis, and in the corn crop. The experimental design was a randomized block design, 11 x 2, with 11 treatments and 2 forage species, and three replications. In the field, the corn was planted at 0.90 m spacing, with interspersed rows of forage plants, and the treatments were applied 15 days after corn emergence (DAE), thus assessing the intoxication observed in the forage plants and corn at 7, 14 and 21 days after application (DAA). At the end of planting, the heights of the ears were also measured. In the greenhouse, a completely randomized design (DIC) was used with the same treatments and the phytotoxicity of the brachiaria was analysed at 15 and 30 DAE, determining the accumulation of dry biomass of the aerial part at 30 DAA. Dose-response curves were also formulated for the herbicide terbuthylazine, in which the intoxication rates of the forage plants U. brizantha, U. ruziziensis and U. decumbens were evaluated at 15 and 30 DAE, for 7, 14, 21 and 28 DAA, and the accumulation of dry mass of the aerial part was determined at 30 DAA. The Scott-Knott test was applied to the analyses and linear regression was applied to the curves. In the field, none of the treatments showed phytotoxicity above 25% after 21 DAA, while in the greenhouse, despite the phytotoxicity associated with the doses, there was no statistical difference between the herbicides in terms of biomass loss by the forage plants. There was no damage to the height of the maize plants. For the control of Althernantera thenella and Ricinus communis in the field, the areas with U. brizantha provided better control associated with the sub-doses of herbicides than U. ruziziensis, which may indicate that this forage has adapted better to the proposed system. Terbuthylazine proved to be selective to forage crops only at 15 DAS.
Effects of using underdoses of herbicides on the control of different species of the Urochloa genus
Keywords: Fitotoxicidade; Forrageira; Integração; Subdose; Terbutilazina; Phytotoxicity; Forage plants; Integration; Underdoses; Terbuthylazine; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA::MATOLOGIA